UDC: 336:658(575.1) THE IMPORTANCE OF MULTIPLIER INDICATORS IN ASSESSING THE EFFECTIVENESS OF THE CASH FLOW OF THE ENTERPRISE - Foziljonov, Ibrokhimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. This article discusses how you can improve your multiprocessor skills. In addition, the scientific basis for determining the financial status of Joint-Stock Companies in our country and their optimal levels based on macroeconomic indicators is given to the multiplier indicators that assess the effectiveness of the cash flow of enterprises. Methods. The multiplicator indicators assessing the effectiveness of cash flows of joint-stock companies were calculated using the calculation of the solvency coefficient, the coefficient of maturity of funds received from their current activities to fulfill obligations, the Bivera coefficient, the coefficient of compensation of short-term liabilities from net profit, and the coefficient of adequacy of net cash flows. Results. According to the results of our research, the normative norm of the bivera coefficient is 0.17-0.4. If the value of the coefficient is in the specified range, the joint-stock company is considered financially stable. If the value of the coefficient is in the range of -0.15 to 0.17, it indicates that the bankruptcy of the joint-stock company is five years away. If the value of the coefficient is less than -0.17, it indicates that the joint-stock company has one year left for bankruptcy. In our analysis, the Bivera coefficient of "Andijan regional power grid enterprise" JSC shows 0.20 in 2021. On the other hand, "Andijan regional power grid enterprise" JSC indicates the stability of the financial situation. Conclusion. It can be said that the assessment of the effectiveness of the company's net cash flows through a direct method of determining the cash flows of Joint-Stock Companies provides an opportunity to assess the effectiveness of the cash flows of a Joint-Stock Company, determine the solvency, the adequacy of net cash flows to finance investment activities.